A New Tool to Evaluate, Improve, and Sustain Marine Protected Area Financing Built on a Comprehensive Review of Finance Sources and Instruments - Bohorquez, John J.; Dvarskas, Anthony; Jacquet, Jennifer; Sumaila, U. Rashid; Nye, Janet; Pikitch, Ellen K. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) require sustained funding to provide sustained marine protection. Up until now government budgets, multi- and bi-lateral aid, and philanthropic grants have been commonly relied upon to finance the management and enforcement of MPAs. But new funding mechanisms, such as impact investments or blue carbon, are increasingly applied and developed. Here, we present a semi-structured review that identifies 11 or more sources of finance, 21 financial instruments and more than 75 potential combinations thereof that show the current diversity of financial mechanisms available to support MPA establishment and operations. Based on the review, we developed nearly 100 indicators reflecting environmental, governmental, socioeconomic, and management characteristics that can inform the appropriateness, and corresponding strengths and weaknesses, of applying these financial mechanisms to any given MPA. The outputs provide a series of recommendations for implementing new funding mechanisms and ways to improve the sustainability of in-place mechanisms. The findings were compiled into a replicable framework and excel tool that was pilot tested in May 2021 for Parque Nacional Natural Corales de Profundidad in Colombia that identified potential ways to improve upon financial mechanisms, including, hiring a full-time manager and potential alternative mechanisms like biodiversity offsets from fossil fuel exploration and exploitation, among several others. The research also identified barriers for implementing financial mechanisms that reflect broader systemic challenges for MPA finance worldwide.